Association of smoking cessation after atrial fibrillation diagnosis on the risk of cardiovascular disease: a cohort study of South Korean men - Seulggie Choi; Jooyoung Chang; Kyuwoong Kim; Sung Min Kim; Hye-Yeon Koo; Mi Hee Cho; In Young Cho; Hyejin Lee; Joung Sik Son; Sang Min Park; Kiheon Lee (BMC, 2020)
Abstract Background While smoking elevates the risk for cardiovascular disease (CVD) among atrial fibrillation (AF) patients, whether smoking cessation after AF diagnosis actually leads to reduced CVD risk is unclear. We aimed to determine the association of smoking cessation after AF diagnosis with subsequent CVD Risk among South Korean men. Methods This retrospective cohort study included 2372 newly diagnosed AF male patients during 2003-2012 from the Korean National Health Insurance Service database. Self-reported smoking status within 2 years before and after diagnosis date were determined, after which the participants were divided into continual smokers, quitters (smokers who quit after AF diagnosis), sustained-ex smokers (those who quit prior to AF diagnosis), and never smokers. Participants were followed up from 2 years after AF diagnosis until 31 December 2015 for CVD. Cox proportional hazards regression was used to determine the adjusted hazard ratios (aHRs) and 95% confidence interval (CIs) for CVD according to the change in smoking habits before and after AF diagnosis. Results The mean (standard deviation, minimum-maximum) age of the study subjects was 62.5 (8.6, 41-89) years. Among AF patients, quitters had 35% reduced risk (aHR 0.65, 95% CI 0.44-0.97) and never smokers had 32% reduced risk (aHR 0.68, 95% CI 0.52-0.90) for CVD compared to continual smokers (p for trend 0.020). Similarly, compared to continual smokers, quitters had 41% risk-reduction (aHR 0.59, 95% CI 0.35-0.99) and never smokers 34% risk-reduction (aHR 0.66, 95% CI 0.46-0.93) for total stroke (p for trend 0.047). Quitters had 50% reduction (aHR 0.50, 95% CI 0.27-0.94), sustained ex-smokers had 36% reduction (aHR 0.64, 95% CI 0.42-0.99), and never smokers had 39% reduction (aHR 0.61, 95% CI 0.41-0.91) in ischemic stroke risk (p for trend 0.047). The risk-reducing effect of quitting on CVD risk tended to be preserved regardless of aspirin or warfarin use. Conclusions Smoking cessation after AF diagnosis was associated with reduced CVD, total stroke, and ischemic stroke risk.